Investigation of Product Performance of Al-Metal Matrix Composites Brake Disc using Finite Element Analysis - Fatchurrohman, Nanang; Marini, C. D.; Suraya, Sulaiman; Iqbal, AKM Asif (2015)
The increasing demand of fuel efficiency and light weight components in automobile sectors have led to the development of advanced material parts with improved performance. A specific class of MMCs which has gained a lot of attention due to its potential is aluminium metal matrix composites (Al-MMCs). Product performance investigation of Al-MMCs is presented in this article, where an Al-MMCs brake disc is analyzed using finite element analysis. The objective is to identify the potentiality of replacing the conventional iron brake disc with Al-MMCs brake disc. The simulation results suggested that the MMCs brake disc provided better thermal and mechanical performance as compared to the conventional cast iron brake disc. Although, the Al-MMCs brake disc dissipated higher maximum temperature compared to cast iron brake disc’s maximum temperature. The Al-MMCs brake disc showed a well distributed temperature than the cast iron brake disc. The high temperature developed at the ring of the disc and heat was dissipated in circumferential direction. Moreover, better thermal dissipation and conduction at brake disc rotor surface played a major influence on the stress. As a comparison, the maximum stress and strain of Al-MMCs brake disc was lower than that induced on the cast iron brake disc.